Beyond Immune Cell Migration: The Emerging Role of the Sphingosine-1-phosphate Receptor S1PR4 as a Modulator of Innate Immune Cell Activation. (7th August 2017) - Olesch, Catherine; Ringel, Christian; Brüne, Bernhard; Weigert, Andreas
Abstract : The sphingolipid sphingosine-1-phosphate (S1P) emerges as an important regulator of immunity, mainly by signaling through a family of five specific G protein-coupled receptors (S1PR1–5). While S1P signaling generally has the potential to affect not only trafficking but also differentiation, activation, and survival of a diverse range of immune cells, the specific outcome depends on the S1P receptor repertoire expressed on a given cell. Among the S1PRs, S1PR4 is specifically abundant in immune cells, suggesting a major role of the S1P/S1PR4 axis in immunity. Recent studies indeed highlight its role in activation of immune cells, differentiation, and, potentially, trafficking. In this review, we summarize the emerging data that support a major role of S1PR4 in modulating immunity in humans and mice and discuss therapeutic implications.